2021
DOI: 10.1038/s43018-021-00226-4
|View full text |Cite
|
Sign up to set email alerts
|

Negative trade-off between neoantigen repertoire breadth and the specificity of HLA-I molecules shapes antitumor immunity

Abstract: The human leukocyte antigen class I (HLA-I) genes shape our immune response against pathogens and cancer. Certain HLA-I variants can bind a much wider range of peptides than others, a feature that could be favorable against a range of viral diseases. However, the implications of this phenomenon on cancer immune response is unknown. In this paper, we quantified peptide repertoire breadth (or promiscuity) of a representative set of HLA-I alleles, and found that cancer patients that carry HLA-I alleles with high … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 85 publications
2
19
0
Order By: Relevance
“…Significant alleles for tumor delay were found to be B∗07:05, C∗07:01, C∗04:01, C∗05:01, C∗16:01, C∗14:02, and C∗17:01. These results are consistent with alleles that are advantageous for tumor suppression in the immune checkpoint inhibitor therapy in previous studies ( Manczinger et al., 2021 ). This finding suggests that differences in the effects of HLA alleles on tumor suppression may affect the immunosurveillance consistency of HLA zygosity.…”
Section: Resutlssupporting
confidence: 92%
“…Significant alleles for tumor delay were found to be B∗07:05, C∗07:01, C∗04:01, C∗05:01, C∗16:01, C∗14:02, and C∗17:01. These results are consistent with alleles that are advantageous for tumor suppression in the immune checkpoint inhibitor therapy in previous studies ( Manczinger et al., 2021 ). This finding suggests that differences in the effects of HLA alleles on tumor suppression may affect the immunosurveillance consistency of HLA zygosity.…”
Section: Resutlssupporting
confidence: 92%
“…They found that HLA-I promiscuity was associated with worse OS and ORR after ICI therapy, mediated by increased expression of immune tolerance genes intratumourally. This aligns with the theory that greater HLA-I promiscuity limits the ability to distinguish self epitopes versus tumour neoepitopes [53]. Once again, HLA-I promiscuity is partly informed by the variety of binding tumour neoepitopes, marrying with the concept of tumour 'immune fitness' and likely varying by tumour histology types [54].…”
Section: Germline Genetic Featuressupporting
confidence: 62%
“…As described here, we (and other groups) observed no association between germline HLA heterozygosity (at the allele or supertype level) or evolutionary divergence and clinical outcomes. Although all the methods applied attempt to capture the diversity of HLA peptide-binding potential in a given patient, none of them account for the variability in the absolute number of peptides a given HLA allele can bind (Paul et al, 2013), also known as HLA allele promiscuity (Manczinger et al, 2021). Future assessments of the impact of germline and somatic (discussed in the next section) HLA diversity may be further refined by taking into consideration the promiscuity of individual alleles.…”
Section: Discussionmentioning
confidence: 99%